Gendered safety nets and growing inequality: Pandemic-induced recession in India - Dev Nathan; S. Rahul (International Labour Organization (ILO), 2022)
In the absence of adequate social security for migrant workers, the recession induced by the COVID-19 pandemic forced the mass return of millions of circular migrants who were supported by their rural households of largely left-behind women. In addition, the recession rendered destitute small traders and operators of microenterprises, and reduced the incomes of small-scale farmers. Based on a study of food supply chains, this paper concludes that gendered rural households functioned as safety nets during the severe recession in the Indian economy, which highlights the weakness in state policy and the lack of resources in the wake of the COVID-19 pandemic. Overall, the recession did not only result in a temporary loss of income but also increased inequality and strengthened the oligopoly structure of the Indian economy.
Keywords: 330; inequality